Adsorptive removal of congo red and methylene blue dyes from aqueous solutions by Rumex obtusifolius roots - Isik, Birol (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2023)
Rumex obtusifolius roots were utilized within the scope of zero waste. Sorption of methylene blue and congo red dyes from wastewater was carried out. First, surface properties were determined using inverse gas chromatography. By this method, it was found that the surface of Rumex obtusifolius roots was acidic (KD/KA=0.13). The point of zero charge value of Rumex obtusifolius roots was determined as 5.62. Based on these results and selectivity studies, suitable dyes were selected for sorption studies. Experimental design was used for the first time to determine the parametric effects and to improve the process for the highest methylene blue and congo red removal. Optimum conditions such as pH (2-12), concentration (10-50 mg/L), adsorbent amount (0.01 g/50 mL-0.30g/50 mL), and contact time (0-210 min) were determined for the adsorption process. The Langmuir-2 model provided the best correlation, and qm values for methylene blue and congo red dyes were determined as 500.00 mg/g and 128.21 mg/g at 298 K. From the kinetic studies, it was found that the sorption process for methylene blue and congo red dyes followed pseudo-second-order kinetics. The effect of NaCl and CaCl2 salts on methylene blue and congo red sorption on Rumex obtusifolius roots was evaluated. The adsorption process was found to be endothermic for methylene blue dye (Delta H-o=+19.33kJ/mol) and exothermic for congo red dye (Delta H-o=-4.99kJ/mol). The process was found to be spontaneous for both dyes (Delta G(o)=-28.10 kJ/mol for methylene blue dye and Delta G(o)=-26.14kJ/mol for congo red dye at 298 K). All findings showed the potential of Rumex obtusifolius roots as a model adsorbent for the removal of various organic pollutants from wastewater.
Keywords: Adsorption; Rumex obtusifolius Roots; Surface Properties; Methylene Blue; Congo Red; SURFACE CHARACTERIZATION; ACTIVATED CARBON; CRYSTAL VIOLET; MALACHITE GREEN; LIQUID-CRYSTAL; CATIONIC DYES; KINETICS; WASTE; WATER; EQUILIBRIUM; Chemistry; Engineering